Strategies for reducing greenhouse gas emissions from municipal solid waste management in Pakistan. Issue 7 (July 2021) - Michel Devadoss, Paul Selvam; Pariatamby, Agamuthu; Bhatti, Mehran Sanam; Chenayah, Santha; Shahul Hamid, Fauziah
The studies on municipal solid waste (MSW) management in Pakistan and its impacts on greenhouse gas (GHG) emissions are glaringly missing. Therefore, this study examines the effect of MSW management on GHG emissions in Pakistan and suggests the best suitable strategies for alleviating GHG emissions. The Intergovernmental Panel on Climate Change (IPCC) 2006 waste model (WM) was used to create inventory of GHG emissions from landfilling. The solid waste management GHG (SWM-GHG) calculator and strengths–weaknesses–opportunities–threat (SWOT) analyses were used as strategic planning tools to reduce GHG emissions by improving MSW management in Pakistan. The IPCC 2006 WM estimated 14, 987, 113 metric tonnes (Mt) carbon dioxide equivalents (CO2 -eq) of GHG emissions in 2016. The SWM-GHG calculator, on the other hand, estimated 23, 319, 370 Mt CO2- eq of GHG emissions from management of 30, 764, 000 Mt of MSW in 2016, which included 8% recycling, 2% composting, and 90% disposal in open dumps. To reduce GHG emissions, two strategies including recycling-focused and incineration-focused were analysed. The recycling approach can reduce more GHG emissions than incineration, as it can reduce 36% of GHG emissions (as compared to GHG emission in 2016) by recycling 23% of MSW, anaerobically digesting 10% of MSW, and disposing of 67% of MSW in sanitary landfills (with energy recovery). Moreover, the SWOT analysis suggested integration of the informal sector, adoption of anaerobic digestion and formulation of explicit MSW regulations for improving the current management of MSW which will also result in lower GHG emissions.